The The Influence of Good Corporate Governance, Green Accounting, and Sustainable Growth on Sustainability Report Disclosure - Freedianingtias Subekti; Surifah Surifah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Good Corporate Governance (GCG), Green Accounting, and Sustainable Growth on the disclosure of sustainability reports among companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research adopts a quantitative approach using secondary data in the form of financial statements and sustainability reports. The sample was selected through purposive sampling, consisting of 100 companies that applied the ASEAN Corporate Governance Scorecard and were among the top 100 firms in terms of market capitalization. Panel data regression with a Random Effect Model was employed as the analytical technique. The findings indicate that both GCG and Green Accounting have a significant positive impact on sustainability report disclosure. In contrast, Sustainable Growth demonstrates a significant negative influence, as its measurement does not directly correlate with the proxies used to assess sustainability disclosure. These results highlight that consistent implementation of sound corporate governance and environmental accounting practices fosters greater transparency in sustainability reporting. However, high levels of sustainable growth do not necessarily align with stronger commitments to sustainability reporting. This study is expected to contribute to the development of sustainability reporting practices and to provide insights for stakeholder decision-making.